The disappearance of hard constraints in neoclassical economics - William M. Wadman (Max Planck Institute of Economics, 2012)
This paper introduces variable quality into the general treatment of neoclassical economics. It also introduces subbudget decision making at all levels. The consequences of these introductions are enormous for traditional theory. Most importantly, is the realization that within the market model there exists the prospect that constraints in capitalism are not hard, nor exclusively determined by market prices. In addition to the above, this paper argues for expansion of demand theory, and for expansion of the theory of general equilibrium. The paper argues against the existence of a hard budget constraint, both for households and for firms; in fact, it argues that the constraint is influenced by subbudget decision making and by the selection of levels of quality, and as such, the constraint may become stochastic, not deterministic. It introduces the proposition that Marginal Rates of Substitution are not equal across consumers; that Marginal Rates of Transformation are not equal across firms; that the condition MRS=MRT is not attainable; that the condition, is not the long-run equilibrium for firms; and it presents arguments against lump-sum taxation, specifically, that the theoretical results of a lump-sum tax are unattainable. The paper introduces additional conditions for attainment of Pareto optimality in welfare economics. Ultimately, the paper argues that market forces are not impartial. This behavior surfaces in consumption space and in input space. This phenomenon arises from human decision making regarding the size of subbudgets and levels of quality, and the model explains how these issues influence the position and slope of constraints in consumption space and in input space. The avenue to attainment of these results lies within what has always been the Achilles tendon of neoclassical economics: the homogeneity assumption, or in this case, the assumption of constant quality and the absence of subbudgets in economic decision making. Insertion of these two elements into neoclassical economics demonstrates that the theoretical foundation of neoclassical capitalism (i.e., the Anglo-Saxon version of capitalism) is itself a special case. These results evolve slowly. Initially, the changes are subtle, but build and emerge forcefully as the paper unfolds. Toward the end of the paper the implication of these findings, in terms of evolution and the human condition, are discussed.
Keywords: 330; Budgetrestriktion; Wirtschaftstheorie; Neoklassik; Theorie